2008
DOI: 10.1083/jcb.200707179
|View full text |Cite|
|
Sign up to set email alerts
|

IKK/NF-κB regulates skeletal myogenesis via a signaling switch to inhibit differentiation and promote mitochondrial biogenesis

Abstract: Nuclear factor κB (NF-κB) is involved in multiple skeletal muscle disorders, but how it functions in differentiation remains elusive given that both anti- and promyogenic activities have been described. In this study, we resolve this by showing that myogenesis is controlled by opposing NF-κB signaling pathways. We find that myogenesis is enhanced in MyoD-expressing fibroblasts deficient in classical pathway components RelA/p65, inhibitor of κB kinase β (IKKβ), or IKKγ. Similar increases occur in myoblasts lack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
155
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 191 publications
(168 citation statements)
references
References 67 publications
10
155
3
Order By: Relevance
“…Consistent with the findings above, analysis of muscles from newborn p65 Ϫ/Ϫ mice (which were maintained on a TNF␣ background to circumvent p65 null lethality and from here on referred to only as p65 Ϫ/Ϫ mice) (27) revealed a significant increase in the total number of myofibers (25). This phenotype suggested that the inhibitory myogenic activity of NF-B is present in the early phases of postnatal muscle development.…”
supporting
confidence: 69%
See 3 more Smart Citations
“…Consistent with the findings above, analysis of muscles from newborn p65 Ϫ/Ϫ mice (which were maintained on a TNF␣ background to circumvent p65 null lethality and from here on referred to only as p65 Ϫ/Ϫ mice) (27) revealed a significant increase in the total number of myofibers (25). This phenotype suggested that the inhibitory myogenic activity of NF-B is present in the early phases of postnatal muscle development.…”
supporting
confidence: 69%
“…In contrast to previous findings where we demonstrated that the absence of p65 in primary myoblasts or silencing of p65 by siRNA in C2C12 myoblasts caused myotube formation to be enhanced (25), here in this co-culture system the total number of myotubes remained the same (supplemental Fig. 4), arguing that fibroblast-derived NF-B activity is responsible for regulating myoblast fusion but is not involved in controlling myogenesis.…”
Section: Nf-b Regulates Inos Expression Within Stromal Fibroblasts Ofcontrasting
confidence: 55%
See 2 more Smart Citations
“…For example, at 48h after acute liver injury in mice, MΦs simultaneously express IL-10 and TNF. During skeletal muscle repair, satellite cells are major targets of TNFα signaling that promotes the early proliferative stage of myogenesis [43]. In the case of heart, TNFα has a cardioprotective function in mice [44].…”
Section: Discussionmentioning
confidence: 99%